2014
DOI: 10.1177/0961203314554849
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of calcineurin inhibitors for the treatment of interstitial lung disease associated with polymyositis/dermatomyositis

Abstract: Interstitial lung disease (ILD) in patients with polymyositis (PM) and dermatomyositis (DM) is often resistant to treatment and life threatening, being recognized as one of the severest complication in these autoimmune disorders. Patients with clinically amyopathic dermatomyositis (CADM) or those with anti-CADM140/MDA5 antibody are especially prone to develop rapidly progressive interstitial pneumonia. We retrospectively analyzed 46 patients with PM/DM admitted to our hospital and identified DM, rapidly progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 79 publications
(113 reference statements)
0
22
0
1
Order By: Relevance
“…A recent retrospective study of 49 Japanese patients with PM/DM-ILD comparing outcomes in patients who received conventional therapy (prednisone with intravenous cyclophosphamide or ciclosporin) versus those who received conventional therapy and tacrolimus found significant improvements in event-free survival in those patients who received tacrolimus. 108 However, as noted in an accompanying editorial, the results may not be generalizable to other populations given the high prevalence of anti-MDA-5-positive disease (40% of IIM-ILD in Japan in one study), a particularly aggressive form of CTD-ILD. 109 110 Furthermore, because more patients in the tacrolimus group received cyclophosphamide, it is unclear whether the improved outcomes were related to cyclophosphamide or tacrolimus.…”
Section: Calcineurin Inhibitorsmentioning
confidence: 86%
“…A recent retrospective study of 49 Japanese patients with PM/DM-ILD comparing outcomes in patients who received conventional therapy (prednisone with intravenous cyclophosphamide or ciclosporin) versus those who received conventional therapy and tacrolimus found significant improvements in event-free survival in those patients who received tacrolimus. 108 However, as noted in an accompanying editorial, the results may not be generalizable to other populations given the high prevalence of anti-MDA-5-positive disease (40% of IIM-ILD in Japan in one study), a particularly aggressive form of CTD-ILD. 109 110 Furthermore, because more patients in the tacrolimus group received cyclophosphamide, it is unclear whether the improved outcomes were related to cyclophosphamide or tacrolimus.…”
Section: Calcineurin Inhibitorsmentioning
confidence: 86%
“…A number of studies have suggested a potential role for calcineurin inhibitors, especially tacrolimus as a first-line and rescue treatment in ILDassociated ASS [109][110][111][112]. Similar regimes have been described in amyopathic DM RP-ILD, including efficacy of combination therapy with cyclosporine and cyclophosphamide [112][113][114][115]. Additional second-line treatments for muscle, skin and subcutaneous disease in other phenotypes include methotrexate, azathioprine and MMF, and in refractory cases intravenous immunoglobulin.…”
Section: Does Clinico-serological Phenotype Influence Outcome and Trementioning
confidence: 97%
“…Use of the former two agents is essentially based on clinical best practice using experience adopted in other conditions such as systemic sclerosis, as well as retrospective observational studies [106][107][108]. A number of studies have suggested a potential role for calcineurin inhibitors, especially tacrolimus as a first-line and rescue treatment in ILDassociated ASS [109][110][111][112]. Similar regimes have been described in amyopathic DM RP-ILD, including efficacy of combination therapy with cyclosporine and cyclophosphamide [112][113][114][115].…”
Section: Does Clinico-serological Phenotype Influence Outcome and Trementioning
confidence: 99%
“…Other myositis-associated antibodies, such as anti-MDA-5, anti-PM-SCL, and anti-Ro-52 are also associated with a higher risk of ILD as well as typical clinical phenotypes. The association between clinically amyopathic dermatomyositis (CADM), anti-MDA-5 positivity, and acute and/or rapidly progressive ILD, which all portend high mortality and poor response to immunosuppression(41, 42) is one of the most prognostically significant, especially in patients of East Asian descent.…”
Section: Treatment Of Ctd-ildmentioning
confidence: 99%